2008
DOI: 10.1098/rspb.2008.0173
|View full text |Cite
|
Sign up to set email alerts
|

Strategic adjustment of begging effort by banded mongoose pups

Abstract: Variation in the intensity of conspicuous displays raises three basic questions: (i) the relationship between internal state and display intensity, (ii) the relationship between display intensity and receiver response, and (iii) the effect of variation in receiver responsiveness on signaller behaviour. Here, I investigate the interaction between pups and helpers in the communally breeding banded mongoose (Mungos mungo), where each pup forms an exclusive relationship with a single adult helper (termed its 'esco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…A recent study shows that banded mongoose pups that are fed by responsive escorts in good condition increase their begging in response to food deprivation more than do pups fed by less responsive escorts in worse condition [36]. These results confirm that costs of care can affect the responsiveness of the carer (in this case not a parent) to begging, and that this in turn can lead offspring to adjust the ESD (in this case probably through learning).…”
Section: Discussionsupporting
confidence: 72%
“…A recent study shows that banded mongoose pups that are fed by responsive escorts in good condition increase their begging in response to food deprivation more than do pups fed by less responsive escorts in worse condition [36]. These results confirm that costs of care can affect the responsiveness of the carer (in this case not a parent) to begging, and that this in turn can lead offspring to adjust the ESD (in this case probably through learning).…”
Section: Discussionsupporting
confidence: 72%
“…Highprovisioning adults were not increasingly likely to feed a heavy pup. This mirrors previous work showing that adults discriminate in their feeding decisions based on an offspring's mass (Sasvàri 1990) or sex (Bell 2008). The ability of pups to move and associate with adults may confound the interpretation of these data, but discrimination of the young can be based on vocal cues alone (Draganoiu et al 2006).…”
Section: Discussionsupporting
confidence: 64%
“…We did not investigate predictors of contribution to pup feeding in meerkats in this paper, but such differences in other species have been predicted by the adult's sex (Davies 1976;Moreno 1984;Edwards 1985 Woxvold et al 2006) and may not depend on the relatedness of the adult to the offspring (Briskie et al 1998;Wright et al 1999;Canestrari et al 2005). Differences in care may be related to differences in sensitivity to offspring need (MacGregor and Cockburn 2002; Mock et al 2005;English et al 2008), adult condition (Sasvàri 1990;Bell 2008) or informational asymmetry (Johnstone and Hinde 2006). The begging rate of meerkat pups varies depending on the identity of the adult they are begging next to, and this is consistent over multiple encounters with the same adult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in biparental systems, these differences may be a consequence of variation in the costs and benefits of care, and are likely to be associated with variation in responsiveness to offspring begging rate. While some studies have investigated how adults in a group vary in their responsiveness to begging according to breeding status or condition ( Wright 1998;Bell 2008), only one study has demonstrated sex differences (MacGregor & Cockburn 2002). To our knowledge, there is no evidence from cooperative breeders that the sex which invests more in the care of young also demonstrates greater responsiveness to increases in begging rate.…”
Section: Introductionmentioning
confidence: 99%